Decision‐making capacity assessment education. Issue 4 (15th February 2021) - Charles, Lesley; Brémault‐Phillips, Suzette; Pike, Ashley; Vokey, Camelia; Kilkenny, Tara; Johnson, Melissa; Tian, Peter G. J.; Babenko, Oksana; Dobbs, Bonnie; Parmar, Jasneet
Abstract: Background/Objectives: As the elderly population and associated number of persons with dementia increase, so does the need for decision‐making capacity assessments (DMCAs). Many healthcare professionals (HCPs), however, do not feel prepared to conduct DMCAs. We have provided 4‐h DMCA workshops to HCPs since 2006 and offered physicians either a 3‐h or 2‐day DMCA workshop from 2013 to present. We evaluated the effectiveness of the workshops on self‐reported key concepts of capacity. Design: Pre‐/post‐test design. Setting: DMCA workshops for physicians across Canada and HCPs within Alberta. Participants: Two hundred and eighty‐one physicians and 835 HCPs. Measurements: Pre‐/post‐workshop ratings on level of comfort with and understanding of 15 core DMCA concepts using 4‐point Likert‐type items. Results: For the DMCA workshops among physicians, ten 3‐h workshops were held in 2014–2015 with 166 participants and seven 2‐day workshops, between 2014 and 2018, with 115 participants. With respect to the self‐report on core DMCA concepts, at least 62.7% (range: 62.7%–89.6%) of physician participants had higher post‐workshop ratings (sign test; p < 0.001) than pre‐workshop ratings for all core DMCA concepts. For the DMCA workshops among HCPs, 4‐h workshops were delivered to 835 HCP participants from 2008 to 2012. At least 49.6% of participants (range: 49.6%–78.9%) had increased post‐workshop ratings (sign test; p < 0.001) for all level of comfort items with and understanding of core DMCA concepts. Conclusion: There is a need for DMCA training for physicians and HCPs. The content and method of the workshops are effective at enhancing self‐reported level of comfort with and understanding of core DMCA concepts.